Left–right asymmetry in the sea urchin. Issue 6 (17th March 2014) - Warner, Jacob F.; McClay, David R.
Summary: The sea urchin is a penta‐radial marine invertebrate of the phylum Echinodermata, yet sea urchins develop initially as bilaterally symmetric embryos and become penta‐radial secondarily during development of the adult. Late in embryogenesis indirectly developing larvae produce molecular asymmetries that dictate the positioning and formation of the adult rudiment on the left side. The rudiment gives rise to the radially symmetric adult during metamorphosis. The mechanism of left–right (L–R) establishment in sea urchin involves highly conserved signaling pathways including Nodal, BMP, Notch, and perhaps Hedgehog. Thus, L–R symmetry‐breaking in the sea urchin appears to utilize a mechanism that is conserved among deuterostomes. At the same time establishment of L–R symmetry in the sea urchin deploys a number of features that are mechanistically unique. Here we review this mechanism and the uncertainties that remain. genesis 52:481–487, 2014. © 2014 Wiley Periodicals, Inc.